2020
DOI: 10.1177/2192568220939523
|View full text |Cite
|
Sign up to set email alerts
|

Complete Versus Incomplete Surgical Resection in Intramedullary Ependymomas: A Systematic Review and Meta-analysis

Abstract: Study Design: Systematic review. Objective: To compare outcomes of complete versus incomplete resection in primary intramedullary spinal cord ependymoma. Methods: A comprehensive search of the MEDLINE, CENTRAL, and Embase databases was conducted by 2 independent investigators. Random-effect meta-analysis and meta-regression with seven covariates were performed to evaluate the reason for the heterogeneity among studies. We also used individual patient data in the integrative analysis to compare complete and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Preoperative neurological condition, tumor size, and extent of resection usually correlate with postoperative neurological condition, but WHO grade does not seem to correlate. [24][25][26] Various studies have been conducted to clarify prognostic factors for SIE. PFS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative neurological condition, tumor size, and extent of resection usually correlate with postoperative neurological condition, but WHO grade does not seem to correlate. [24][25][26] Various studies have been conducted to clarify prognostic factors for SIE. PFS.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative neurological condition, tumor size, and extent of resection usually correlate with postoperative neurological condition, but WHO grade does not seem to correlate. 24-26 Various studies have been conducted to clarify prognostic factors for SIE. 8,13-23 Several prognostic factors for longer PFS including histopathological type, extent of resection, tumor size, or preoperative neurological condition have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous studies have discussed the predictors of surgical outcomes in patients with spinal ependymomas, the majority of existing evidence focuses on tumor recurrence and overall survival [18,15,[22][23][24], and investigations concerning neurological functions remain limited [5,19,24]. In 2011, Boström and colleagues retrospectively analyzed functional outcomes in 57 cases of spinal ependymoma, in which complete resection was gained in 83% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Ge et al found that the neurological deterioration rate was signi cantly higher in patients undergoing subtotal resection than that in the patient receiving gross total resection (P = 0.011) [10]. Recently, Salari et al performed a systematic review involving 407 cases in 23 studies; the authors concluded that complete surgical resection of intramedullary spinal cord ependymoma could prolong the progressionfree survival (P = 0.004) and improve follow-up neurological functions (P = 0.019) in comparison with incomplete resection [19]. In the current study, 51 (94.4%) patients achieved gross total resection, and incomplete resection was only performed in 3 (5.6%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed protocol has been published in PROSPERO (CRD42018103513) to study "Biopsy vs resection for intramedullary spinal cord tumors" and a systematic review specifically on intramedullary ependymoma has been performed according to the protocol. 6 Simultaneously, we conducted a systematic review of intramedullary astrocytoma based on the same protocol and the records identified by searching databases. In the section below, we provided a summary of the method used.…”
Section: Methodsmentioning
confidence: 99%